The immunomodulatory effects of Qushi Jianpi Hewei Decoction (QJHD) for patients with COVID-19 by metagenomics and transcriptomic sequencing - Jinhui Li; Yichang Yang; Bing Xiong; Jing Lu; You Zhou; Caixia Li; Xiao Hu (Elsevier, 2022)
Ethnopharmacological relevance: Several studies have confirmed that intestinal microflora dysbiosis correlates with the severity of COVID-19 patients. Clinical meta-analysis and our data show that the circulating miRNAs like miRNA-146 and the levels of serum cytokines in the peripheral blood are closely related to mild to moderate COVID-19 patients. Despite the widespread use of traditional herbal medicine for COVID-19 in China, the mechanisms remain largely uncovered. Aim of the study: We conducted an observational case-control study to verify the efficacy and safety of traditional Chinese herbal medicine Qushi Jianpi Hewei Decoction (QJHD) for mild to moderate COVID-19 patients, and investigated the potential biomolecular mechanisms through metagenomics and transcriptomic sequencing methods. Materials and methods: QJHD was given orally twice a day individually for 14 to 28 days. A total of 10 patients were enrolled in the study and given QJHD. We observed advantages in clinical cure time rate, and the relief of gastrointestinal symptoms as compared with reports in the literature. The metagenomics sequencing data of fecal microflora and transcriptomic sequencing data of blood cell in patients with SARS-Cov-2 infection patients were selected compared to the healthy control donors. Results: No serious adverse events were reported. Meanwhile, the transcriptome analysis showed a decrease of the hsa-miR-21-5p expression in peripheral blood without QJHD. The species composition analysis showed an increase in the expression of Faecalibacterium prausnitzii in the intestinal tract; The interleukin-10 (IL-10) expression also in COVID-19 patient decreased in peripheral blood compared with healthy control donors. And we found an improvement in these parameters in patients taking QJHD. Conclusions: Our findings show that QJHD could improve clinical outcomes of mild to moderate COVID-19 patients, probably through beneficial immunomodulatory effects by regulating Faecalibacterium prausnitzii in the intestinal tract and hsa-miR-21 and IL-10 expression in peripheral blood. (chictr.org.cn, ChiCTR2000030305)